1999
DOI: 10.1002/(sici)1097-0231(19991130)13:22<2237::aid-rcm780>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of exogenous dehydroepiandrosterone excretion in urine by gas chromatography/combustion/isotope ratio mass spectrometry

Abstract: A detailed procedure for the analysis of exogenous dehydroepiandrosterone (DHEA) in urine by gas chromatography/combustion/isotope ratio mass spectrometry (GC/C/IRMS) has been established for detecting doping with DHEA. The average delta-value (parts per thousand difference of (13)C/(12)C ratio from the isotope ratio standard) of 26 synthetic steroids commercially available was -30.1 +/- 2.6, and was significantly lower than that of human endogenous DHEA in urine of the world class athletes who had participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 13 publications
6
80
0
Order By: Relevance
“…Derivatisation with O-ethylhydroxylamine was investigated for determination of etiocholanolone (E) and androsterone (A) [51], and Ueki and Okano [17] investigated PD, 5a and 5b excreted glucuronidated and added dehydroepiandrosterone sulfate (DHEA_S) to the scope of IRMS methods using a TEAP-LH20 anion exchange column.…”
Section: Irms Methods Developed and Used In Sports Drug Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Derivatisation with O-ethylhydroxylamine was investigated for determination of etiocholanolone (E) and androsterone (A) [51], and Ueki and Okano [17] investigated PD, 5a and 5b excreted glucuronidated and added dehydroepiandrosterone sulfate (DHEA_S) to the scope of IRMS methods using a TEAP-LH20 anion exchange column.…”
Section: Irms Methods Developed and Used In Sports Drug Testingmentioning
confidence: 99%
“…2, the difference between endogenous and synthetic steroids is not always large enough to allow them to be distinguished. Whereas endogenous steroids reflect the CIR of a mixture of C 3 and C 4 plants, synthetic steroids should exhibit a clear single C 3 signature, resulting in values lower than −26.5‰ [17,18]. Some rare cases have been reported with steroids exhibiting δ 13 C values in the endogenous range [61,82] and recently a comprehensive investigation on seized T samples showed that nearly 10% of all T preparations were enriched more than −25‰ [81].…”
Section: H/ 1 H Ratios Of Endogenous Urinary Steroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the last years, the number of investigations on carbon isotope ratios (CIR) of endogenous urinary steroids in the context of sports drug testing has considerably increased [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Regarding absolute values expressed as δ 13 C VPDB against the international standard Vienna Pee Dee Belemnite (VPDB) based on Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation of natural (endogenous) from synthetic (exogenous) hormones -AASs steroidal products yielded δ 13 C values of -30.1‰ ± 2.6‰ and -25.9‰ to -32.8‰ (Ueki and Okano 1999;de la Torre et al 2001); however, δ 13 C values reflecting typical 'human' CIRs were also reported (Cawley et al 2010;Forsdahl et al 2011) representing an additional challenge for doping control authorities. To account for the fact that diets vary considerably, and thus also δ 13 C values of urinary steroids, endogenous reference compounds (ERCs), i.e.…”
Section: Analytical Aspectsmentioning
confidence: 98%